INVESTIGATING THE FACTORS THAT INFLUENCE ANGER AND FRUSTRATION OF THE CUSTOMERS - Mudassar Abbasi, Dr. Muhammad; Kausar, Tayyiba; Hoque, Akramul (The journal of contemporary issues in business and government, 2022)
This research focuses on the association between factors that influence the anger and frustration of the customer in the restaurant. Anger is a feeling that ranges from mild to severe exasperation ferocity and anger and frustration is the reaction to be sad or angry as a result of not being able to change or do something thing. Through random sampling technique, we selected 197 respondents from different departments of Punjab University Lahore. Survey method by distributing questionnaires was utilized for collection of data. Descriptive along with Inferential Statistics was used to analyze results. Results of the study displayed positive and notable connections among all independents and dependent variable except one independent construct which was High Price. Present study identified the impact of environmental conditions of the restaurant towards anger frustration and dissatisfaction of their consumers.